IVO GOLDSTEIN, ANTISEMITIZAM U HRVATSKOJ OD SREDNJEGA VIJEKA DO DANAS [ANTI-SEMITISM IN CROATIA FROM THE MIDDLE AGES TO THE PRESENT] (ZAGREB: FRAKTURA AND THE “BET ISRAEL” JEWISH RELIGIOUS COMMUNITY IN CROATIA, ZAPREŠIĆ AND ZAGREB, 2022), 632 PAGES” (Review of Croatian History, 2022)
REVIEW